Advances in innovative seed potato production systems in India - Buckseth, Tanuja; Tiwari, Jagesh K.; Singh, Rajesh K.; Kumar, Vinod; Sharma, Ashwani K.; Dalamu, Dalamu; Bhardwaj, Vinay; Sood, Salej; Kumar, Manoj; Sadawarti, Murlidhar; Challam, Clarissa; Naik, Sharmistha; et al. (Frontiers in Agronomy, 2022)
India is the second-largest producer of potatoes in the world, accounting for 11.3% of the total global potato area and contributing 12.5% to global potato production. Seed is a single most important input in potato cultivation. High seed rate (2.5 -3.0 t/ha), low rate of multiplication, progressive viral degeneration, storage, and transportation are major issues of potato seed production in the country. Potato seed alone accounts for 40-50% of the total potato production cost and also, huge quantities of edible food is put back in the soil as potato seed. Delayed reach of new improved varieties to the farmers’ fields due to slow multiplication rate and frequent seed replacement because of degeneration are associated issues. To circumvent these issues, continuous efforts are being made by the potato researchers to develop innovative technologies for quick multiplication of initial healthy breeder’s seed of the released varieties in sufficient quantities to meet the demand in our country. A paradigm shift in potato seed production methods has taken place globally since the early 1900s. Major potato producers of the world have shifted from conventional to the hi-tech seed production system to improve the seed quality and enhance seed multiplication rate. New innovations can overcome many of the problems associated with potato seed production, particularly in tropical and sub-tropical countries. Recent advances in potato seed production systems in India and challenges ahead for seed production are described here.